Pengelompokan Persediaan Barang dengan Metode FSN Analysis (Fast, Slow and Non-moving) Berdasarkan Turn Over Ratio (TOR) - M Hudori; Niro Tami B Tarigan (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
This research discusses classification of inventory in a warehouse of palm oil plantation company located in Central Kalimantan Province. The purpose of this research is to classify inventory of goods by the method of FSN Analysis (Fast, Slow and Non-moving) based on turn over ratio (TOR) and how to control these goods. The method used is quantitative analysis based on historical data using the FSN Analysis and TOR methods. The result showed that the classification of inventory by the method produced three classify of goods, ie fast-moving, slow-moving and non-moving. The three classify of goods need different management system. The goods in the fast-moving that a large quantity of need can be managed by applying safety stock and reorder point, while that small quantity and items in the slow-moving can be managed by the periodic review (R, s, S) power method approximation or can be bought when needed. While goods in the non-moving are sufficient to be purchased when needed, while still taking into quantity and schedule of demand so that no stockout conditions occur.